Targeting Wnt-driven metabolic adaptations in cancer: integrating glycolysis, glutaminolysis, IDO1-mediated immune evasion, and therapeutic delivery strategies - Flores-Hernández, Eric; Binder, Grace; Mei, Kuo-Ching; Tejeda-Muñoz, Nydia (Frontiers in Cell and Developmental Biology, 2025)
The Wnt pathway is an evolutionarily conserved signaling cascade that regulates a wide range of fundamental cellular processes, including proliferation, differentiation, polarity, migration, metabolism, and survival. Due to its central regulatory roles, Wnt signaling is critically involved in the pathophysiology of numerous human diseases. Aberrant activation or insufficient inhibition of this pathway has been causally linked to cancer, degenerative disorders, metabolic syndromes, and developmental abnormalities. Wnt signaling drives cancer progression by reprogramming metabolism and promoting immune evasion. Wnt-driven tumors exhibit enhanced aerobic glycolysis (the Warburg effect), glutaminolysis, and macropinocytosis, which support rapid proliferation and help maintain redox homeostasis under nutrient-limited or nutrient-deprived conditions. These metabolic adaptations sustain tumor survival and contribute to immune suppression, as seen in the Wnt5a-indoleamine 2,3-dioxygenase 1 (IDO1) axis, which fosters regulatory T-cell expansion and an immunosuppressive microenvironment. The interplay among glycolysis, glutamine metabolism, and immune escape renders Wnt-driven cancers highly adaptable and resistant to conventional therapies. Targeting metabolic enzymes, such as pyruvate dehydrogenase kinase 1 (PDK1), lactate dehydrogenase A (LDHA), glutaminase (GLS), and monocarboxylate transporters (MCT-1), alongside immune checkpoint inhibitors or IDO1 blockade, presents a promising strategy for overcoming metabolic plasticity and immune evasion in Wnt-driven malignancies, thereby enhancing therapeutic efficacy and improving patient survival in otherwise refractory tumor types. Combining glycolysis and glutaminolysis inhibitors with T-cell activating therapies may disrupt tumor metabolic plasticity and restore anti-tumor immunity. Additionally, advanced drug delivery systems, including lipid nanoparticles (LNPs), polymeric nanocarriers, and exosome-based platforms, enhance the targeted accumulation of metabolic inhibitors and immunomodulatory agents while minimizing systemic toxicity. This review examines the metabolic and immune adaptations of Wnt-driven cancers, with a focus on glycolysis, glutaminolysis, and macropinocytosis. We highlight emerging therapeutic targets and nanomedicine-based delivery strategies to counteract metabolic adaptation and immune suppression. By integrating metabolic and immune-targeting with precision nano-delivery platforms, future treatment paradigms may improve outcomes for aggressive and therapy-resistant Wnt-driven cancers.